2007
DOI: 10.1542/peds.2006-3780
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Preparedness of US Emergency Departments: A 2003 Survey

Abstract: Pediatric preparedness of hospital emergency departments demonstrates opportunities for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(176 citation statements)
references
References 14 publications
6
167
0
3
Order By: Relevance
“…Although 90% of children are seen in nonpediatric-focused EDs in the United States, more than half of EDs see fewer than 6 patients per day. 34 An association between higher volumes and better outcomes has been reported for certain types of pediatric health care. [35][36][37][38][39] Whereas volume per se does not lead to better outcomes in health care, it is a proxy measure for other factors including the accumulation of experience by individual providers, 39,40 and organizational and structural attributes of hospitals.…”
Section: Figurementioning
confidence: 97%
“…Although 90% of children are seen in nonpediatric-focused EDs in the United States, more than half of EDs see fewer than 6 patients per day. 34 An association between higher volumes and better outcomes has been reported for certain types of pediatric health care. [35][36][37][38][39] Whereas volume per se does not lead to better outcomes in health care, it is a proxy measure for other factors including the accumulation of experience by individual providers, 39,40 and organizational and structural attributes of hospitals.…”
Section: Figurementioning
confidence: 97%
“…In the United States, the vast majority of children are cared for in non-pediatric hospital emergency departments, emergency departments that are located in general hospitals rather than in hospitals dedicated to the care of children (American Academy of Pediatrics, Committee on Pediatric Emergency Medicine, 2007;Gausche-Hill, Schmitz, & Lewis, 2007).…”
Section: Demographicsmentioning
confidence: 99%
“…In 2007, a survey which assessed the degree of pediatric preparedness of emergency departments in the United States showed that 89% of pediatric visits occurred in nonchildren's hospitals, 26% of visits occurred in rural or remote facilities and 75% of emergency departments saw less than 7000 children per year (Gausche-Hill et al, 2007).…”
Section: Demographicsmentioning
confidence: 99%
“…Additionally, few general hospitals provide training in pediatric emergencies, and less than 6% possess a full complement of child-appropriate equipment, medications, and supplies. [75][76][77] Branson discussed whether sick children can be managed as adult patients, and said that the answer depends on the specific hospital, the child's age and weight, and the pathophysiology of the disease or injury.…”
Section: Disaster Planning For Pediatricsmentioning
confidence: 99%